Suffruticosol B from Paeonia lactiflora Ameliorates Alzheimer's Disease Pathology by Inhibiting MAO-B Activity - Heo, Jaejun; Han, Young-Eun; Kim, Min Soo; Eunji Cheong; Chun Whan Choi; Oh, Soo-Jin (John Wiley & Sons Inc., 2025)
Monoamine oxidase B (MAO-B) has emerged as a therapeutic target for Alzheimer's disease (AD) due to its involvement in the synthesis of γ-aminobutyric acid (GABA) in reactive astrocytes, which inhibits neuronal activity. Suffruticosol B (Suf-B), isolated from Paeonia lactiflora, is one of the resveratrol oligomers. Although resveratrol oligomers have demonstrated neuroprotective effects, it remains unexplored whether Suf-B exerts therapeutic effects on AD by targeting MAO-B. In this study, we investigated whether Suf-B alleviates AD pathology by mitigating reactive astrogliosis and inhibiting the overproduction of astrocytic GABA. After confirming the MAO-B inhibitory effect of Suf-B through MAO-B enzyme assay, we administered Suf-B to APP/PS1 AD model mice. To test the potential therapeutic action of Suf-B in AD, a series of experiments were conducted, including behavioral tests such as the open field test, novel object recognition test, Barnes maze test, passive avoidance test, as well as immunohistochemistry and whole-cell patch-clamp recordings. We found that Suf-B markedly inhibited MAO-B activity without causing cytotoxicity. Immunohistochemistry and electrophysiology experiments demonstrated that Suf-B significantly reduced astrocyte reactivity, as well as an aberrant increase in GABA production and tonic GABA release from astrocytes in AD. Behavior test results indicated that Suf-B treatment restored cognitive function in APP/PS1 mice. In conclusion, Suf-B effectively reduces excessive GABA production in reactive astrocytes by inhibiting MAO-B, normalizing aberrant inhibition in hippocampal neurons in an AD mouse model. These results suggest that Suf-B has potential as a treatment for AD and may be applicable to other brain diseases associated with reactive astrogliosis.